Combining a dynamic battery model with high-resolution smart grid data to assess microgrid islanding lifetime. (1st January 2015) - Fares, Robert L.; Webber, Michael E.
Highlights: A dynamic battery model is used to describe a transformer-level grid battery system. Smart grid data is used to simulate the battery system operating in islanded mode. Thousands of islanding events are simulated to show the expected islanding lifetime. 50 kW h transformer-level storage alone can endure 93% of average-duration outages. Adding rooftop solar does not increase islanding lifetime during peak hours. Abstract: In this paper, we use experimental data collected from an Austin, Texas smart grid test bed with a system-level battery energy storage model to assess the lifetime of batteries in a microgrid operating in islanded mode during a distribution-level outage. We consider a hypothetical microgrid consisting of 21 single-family detached homes and three transformer-level community energy storage (CES) battery units ranging in size from 25 kW h to 75 kW h. To describe the performance of CES batteries, we implement a dynamic behavioral circuit model capable of describing voltage transients and rate-capacity effects. We use one-minute electricity production and consumption data collected from the smart grid test bed in 2012 to assess how the timing of an electric outage affects the islanding lifetime of a residential microgrid. We contrast our results with the average outage duration reported by U.S. electric utilities to quantify how often a residential microgrid could withstand a typical outage. Our results show that increasing the amount of rooftop PV in a residential microgrid does not significantly increase how often it can withstand an average-duration outage. However, combining PV with CES extends the median islanding lifetime by up to 11.6 h during morning outages. Based on our results, 50 kW h CES provides the best tradeoff between the cost of a CES system and its reliability benefit, allowing downstream loads to withstand an average-duration outage approximately 93% of the time.